Posouzení informačního systému firmy a návrh změn - Stuchlíková, Tereza (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Bakalářská práce se zabývá posouzením docházkového informačního systému provozních zaměstnanců firmy ČEZ a. s. v Jaderné elektrárně Dukovany a návrhem změn pro tuto část informačního systému. První část bakalářské práce definuje základní pojmy a teoretická východiska. Druhá část obsahuje analýzu současného stavu záskokového systému a třetí poté návrhy na zlepšení, eliminaci rizik a ekonomické zhodnocení návrhů.

This bachelor thesis deals with the evaluation of an information system keeping attendance of the employees of the ČEZ a. s. company at the Dukovany Nuclear Power Station and offers proposals for its improvement. The first part of the work defines the basic terminology and the theoretical basis for further use. The second part includes an analysis of the current state of the system for substitution of workers and the last one proposes areas for improvement and elimination of risks and assesses the economical aspect of these proposals.
Information System Assessment and Proposal of ICT Modification
Keywords: data; informace; informační systém; SWOT analýza; HOS analýza; data; information; information system; SWOT analysis; HOS analysis